A Synoviocyte Model for Osteoarthritis and Rheumatoid Arthritis: Response to Ibuprofen, Betamethasone, and Ginger Extract—A Cross-Sectional In Vitro Study. (31st December 2012) - Ribel-Madsen, Søren; Bartels, Else Marie; Stockmarr, Anders; Borgwardt, Arne; Cornett, Claus; Danneskiold-Samsøe, Bente; Bliddal, Henning
Abstract : This study aimed at determining if synovial cell cultures from rheumatoid arthritis (RA), osteoarthritis (OA), and healthy controls (HC) differ and are suitable disease models in pharmacological studies, and tested their response to some anti-inflammatory drugs. Synovial cells were isolated from synovial membrane or joint fluid. Cells were cultivated and exposed to no or TNF- α stimulation without, or in the presence of, betamethasone, ibuprofen, or a standardized ginger extract. Concentrations of a panel of cytokines, growth factors, and chemokines were mapped for each culture and condition. Our cells secreted an increased amount of the cytokines IL-1 β, IL-6, and IL-8 in response to TNF- α stimulation in all conditions. OA cells showed a higher IL-6 and IL-8 and a lower IL-1 β production, when not stimulated, than RA and HC cells, which were similar. TNF- α stimulation caused similar IL-1 β, IL-6, and IL-8 release in all groups. Ibuprofen showed no effect on cytokine production, while ginger extract was similar to betamethasone. Ginger extract was as effective an anti-inflammatory agent as betamethasone in this in vitro model. Cultured fibroblast-like synoviocytes from OA and RA subjects promise to be a useful pharmacological disease model, but further studies, to support results from such a model are needed.